Impact of Hydro Peaking Operation on Downstream RoR Energy Generation in West Seti River Basin - Mahat, Brabina; Baniya, Rupesh; Regmi, Ram Krishna (Journal of Advanced College of Engineering and Management, 2026)
Nepal’s power system is dominated by run-of-river (RoR) hydropower projects, challenging load management during peak hours. Amidst prioritization of government policy to Peaking RoR scheme, there is a lack of proper framework for analyzing downstream linkages of hydro-peaking in a river basin. Daily peaking operation of a RoR project will have substantial impact on downstream project but has been less considered in regional studies. This study analyzes the impact of peaking operation on flow availability and subsequent energy generation considering two projects; Chainpur Seti and Seti-Nadi3 HPP of West Seti river basin. This study analyzes two operational scheme; one with complete stoppage of upstream plant for reservoir filling and another reservoir filling by continuous withdrawn on non-peak hours for storage. For the operation Scheme 1, during normal condition the generation loss is 17%, 19% while considering the flushing effect, 16.9% when turbine operation is considered, and 19.2% when both flushing and turbine operation are taken in consideration. Similarly, for operation Scheme 2, the generation loss is 0.97% for normal condition, 3.3% when flushing effect is considered, 0.36% when turbine efficiency only is considered, and 2.8% when both the flushing effect and turbine operation is taken into account. Also, the generation of downstream project shows increasing trend only when the peaking hours is greater than or equal to 2hr. Our study necessitates the multi-stakeholder collaboration in planning and operation at project and basin level for sustainable water resources management.